Assessment of the decellularized extracellular matrix (dECM) from the skin of yellowfin tuna (Thunnus albacares) - Barlisan, Chancy Louisse T.; Bual, Ronald P.; Don Valle, Kit Dominick; Bacosa, Hernando P. (2024)
Fish processing industries produce a wide range of by-products such as skin, bones, and viscera. These wastes contain bioactive components and are a potential source of biomaterial scaffolds. Thus, the utilization of the fish skin was employed for sustainable solutions to waste management and biomedical material sourcing. The study aims to supplement the limited data on the assessment of yellowfin tuna skin for developing decellularized extracellular matrix (dECM) by evaluating the efficiency of a chemical decellularization method using 0.1% sodium dodecyl sulfate (SDS). Moreover, the data indicated a reduction in cellular components in dECM, as shown in the H&E staining images. The FTIR spectra confirmed the preservation of the collagen triple helix structure. Similarly, SEM imaging revealed the preserved structural integrity of the dECM. The DSC results highlighted the thermal stability of dECM tuna skin, crucial for withstanding body temperature and inflammation during processing and transplantation. These findings underscore the potential of dECM tuna skin as a sustainable biomaterial with diverse biomedical applications, emphasizing its structural, functional, and thermal resilience. Further research is necessary to optimize the decellularization process and evaluate the biocompatibility, immunogenicity, mechanical properties, and in vivo applicability of the tuna skin-derived dECM for comprehensive insights into its suitability for specific biomedical applications.
Keywords: Yellowfin tuna; Waste management